Effects of an astaxanthin‐containing supplement on oxidative status in skeletal muscle and circulation during deconditioning and reconditioning periods in polo ponies - Mia Y. Kawaida; Oh. Sung Kwon; Ahram Ahn; Amanda S. Reiter; Nicole M. Tillquist; Sung Gi Noh; Jung W. Lee; Timothy E. Moore; Sarah A. Reed (Physiological Reports)
Abstract This study investigated the effects of astaxanthin (ASTX) supplementation on oxidative status during a deconditioning‐reconditioning cycle. Twelve polo ponies were assigned to no supplementation (CON) or an ASTX supplemented group, which received oral administration of a supplement containing 75 mg ASTX daily for 32 weeks. Polo ponies underwent a 16‐week deconditioning period (DECON) followed by a 16‐week reconditioning program (RECON). Submaximal exercise tests (SETs) were performed at the beginning of the study (Baseline), after DECON, and after RECON. Blood samples were collected at −30, 0, 15, 30, and 60 min relative to each SET for oxidative status analysis. Muscle samples were collected 2 weeks before (Pre‐Ex) and 2 h after (Post‐Ex) each SET for muscle oxidative status and gene expression analyses. Pre‐Ex muscles were analyzed for high‐resolution respirometry. Circulating glutathione peroxidase (GPX) activity was increased (p ≤ 0.02) and protein carbonylation was decreased in ASTX (p ≤ 0.05). Muscle oxidative status was affected by DECON and reconditioning (p ≤ 0.05). ASTX increased gene expression of PPARGC1A after reconditioning (p ≤ 0.05). Deconditioning reduced oxidative phosphorylation at complex I and II (p = 0.01). Thus, a deconditioning‐reconditioning cycle had greater impacts on muscle oxidative capacity than ASTX supplementation.